Efektivitas Manajemen Penjaminan Mutu Pendidikan di SMK Bakti Karya - Acep Wildan Mubarok; Meilina Silvi Imanika; Gilang Prasetya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
Assuring the quality of education is a crucial aspect in improving the quality of education and the success of educational institutions. This research aims to evaluate the effectiveness of education quality assurance management at Bakti Karya Vocational School. The research method used is a qualitative approach with descriptive analysis, involving direct observation, interviews with related parties, and documentation studies. The research results show that Bakti Karya Vocational School has implemented various quality assurance procedures which include planning, implementing and evaluating educational activities. However, there are several challenges in its implementation, such as limited resources and lack of training for teaching staff. This research recommends increasing training for teaching staff, preparing more detailed operational standard guidelines, and utilizing information technology to support the quality assurance process. In conclusion, although quality assurance management at Bakti Karya Vocational School shows significant progress, it needs continuous improvement and refinement in order to achieve optimal educational results.